(untitled) (International Journal of Food and Nutritional Sciences, 2021)
To improve patient compliance, direct compression was used in this study to manufacture oral dispersible cinnarizine tablets. The proposed effort aims to create Cinnarizine orally dispersible tablets for fast drug absorption and dissolution, perhaps leading to a quick beginning of action in the treatment of motion sickness. Studies measuring the compatibility of drugs and excipients using FTIR measurements. The medication content, weight variation, friability, hardness, wetting time, and in vitro disintegration time of these tablets were assessed. In comparison to other formulations, the tablets from batch F1 that included crosscaramellose had improved organoleptic qualities as well as outstanding in-vitro disintegration time and drug release.